2006
DOI: 10.1080/14017430600746276
|View full text |Cite
|
Sign up to set email alerts
|

Composite aortic root replacement using the classic or modified Cabrol coronary artery implantation technique

Abstract: We conclude that composite aortic root replacement with the classic or modified Cabrol technique results in a low operative mortality. However, it should be only used when a "button" technique is not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Only a few studies have reported the outcomes of the technique described in this study. Garlicki et al report a 0% early mortality in their series of 19 patients following the modified Cabrol technique, 22 whereas a larger series of 45 patients by Nakahira et al report an early mortality of 5% 19 . The former study, however, does not elaborate on the premorbid state of their patients nor their indications for a root replacement.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only a few studies have reported the outcomes of the technique described in this study. Garlicki et al report a 0% early mortality in their series of 19 patients following the modified Cabrol technique, 22 whereas a larger series of 45 patients by Nakahira et al report an early mortality of 5% 19 . The former study, however, does not elaborate on the premorbid state of their patients nor their indications for a root replacement.…”
Section: Discussionmentioning
confidence: 97%
“…Tension on the coronary ostia is avoided using this interposed graft. Although the operative feasibility of this technique is promising, only few studies have shown the midterm outcomes of this technique 19,22 …”
Section: Discussionmentioning
confidence: 99%
“…Major valve-related adverse event 7 studies were included, with a random effects model combining MAVRE of 2.32% (per patient-year), a 95% con dence interval of (1.04-5.16) and a heterogeneity I 2 of 76.5% [6, 9,14,22,[24][25]27]. (Fig.…”
Section: Root Reoperationsmentioning
confidence: 99%
“…Kourliouros et al [ 19 ] introduced the “T-fashion” modification. Meanwhile, the Cabrol procedure and its modifications have been tested and confirmed to be safe and effective [ 17 , 20 23 ]. It’s currently indicated when traditional button implantation is difficult, such as fragile or torn coronary ostia.…”
Section: Introductionmentioning
confidence: 99%